2016
DOI: 10.1021/acssuschemeng.6b00669
|View full text |Cite
|
Sign up to set email alerts
|

Enriching Heteroelements in Lignin as Lubricating Additives for Bioionic Liquids

Abstract: Depolymerization and modification of lignin have been achieved simultaneously in a one-pot chemical reaction. Two heteroelement-rich modifiers, imidazol-1-yl phosphonic dichloride and 1H-1,2,4-triazol-1-yl phosphonic dichloride, were selected to react with lignin in this work. The modified lignin (m-lignin) is demonstrated as an effective lubricating additive for [choline]­[amino acid] ([CH]­[AA]) bioionic liquids. Different characterization techniques have been utilized to study the lignin depolymerization, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Polymer blending is an effective way to increase the density of H-bonds because one component polymer can supply donating group while the other to supply accepting groups. Biopolymers in which the H-bond molecular group exist widely are usually applied in polymer blends, such as gelatin which possesses abundant carboxylic, amide, and amine groups, [46][47][48] lignin which owns abundant hydroxyl and aldehyde groups [49,50]. The H-bond density and the mixture ratio of polymer blends could strongly affect the thermal conductivity.…”
Section: Hydrogen Bondmentioning
confidence: 99%
“…Polymer blending is an effective way to increase the density of H-bonds because one component polymer can supply donating group while the other to supply accepting groups. Biopolymers in which the H-bond molecular group exist widely are usually applied in polymer blends, such as gelatin which possesses abundant carboxylic, amide, and amine groups, [46][47][48] lignin which owns abundant hydroxyl and aldehyde groups [49,50]. The H-bond density and the mixture ratio of polymer blends could strongly affect the thermal conductivity.…”
Section: Hydrogen Bondmentioning
confidence: 99%
“…Both rGO and PEG contain polar groups which provide effective dispersion stability through hydrogen bonding. Moreover, PEG is widely used in biomedical applications for reducing the friction and wear of knee joints1819, but the use of rGO as blend additive to PEG for biomedical applications needs to be thoroughly investigated in term of safety7. The interaction mechanism of hydroxyl-hydroxyl and epoxy-hydroxyl terminated rGO with PEG were investigated.…”
mentioning
confidence: 99%
“…The overall philosophy herein is to assist deconstruction of lignocellulosic material via covalent modifications, thus generating functional secondary building blocks. For instance, Zhu et al 90 reported on the phosphorylation of kraft lignin for the preparation of new lubricant additives. As shown in Scheme 11 , the authors exploited hydrogen chloride, which is generated in situ during the synthesis of (imidazol-1-yl)phosphonic dichloride, to hydrolyze ether bonds (typically β- O -4 bonds; Scheme 9 ).…”
Section: From Raw To Functionalized Ligninmentioning
confidence: 99%
“…Besides the incorporation of new functionalities and the decrease in molecular weight, the solubility of such functional lignin in polar solvents could be significantly improved. 90 …”
Section: From Raw To Functionalized Ligninmentioning
confidence: 99%